The Effect of Macroeconomic and Microeconomic Variables on the Profitability of Sharia Commercial Banks in Indonesia - Nurrosyida Latifa Himma; Tiara Juliana Jaya (Maliki Islamic Economics Journal, 2024)
This study aims to determine the influence of macro and microeconomic variables on the profitability of Sharia Commercial Banks in Indonesia. The sample determination in this study used purposive sampling techniques and produced seven samples of Sharia Commercial Banks used in this study. The dependent variables used consist of inflation, interest rates, Gross Domestic Product (GDP), Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Expense to Operating Income (OEOI). The data analysis method used is panel data regression with e-views software version 12. The results of this study show that interest rate, GDP, and OEOI variables partially have a significant effect on the profitability of Sharia Commercial Banks, while inflation, NPF, and FDR variables partially do not have a significant effect on the profitability of Sharia Commercial Banks in Indonesia in 2017-2021. Meanwhile, based on the results of simultaneous tests, it was found that the variables of inflation, interest rates, GDP, NPF, FDR, and OEOI had a significant effect on the profitability of Sharia Commercial Banking 2017-2021.